Experimental archaeology (Oxford)
vi, 105 sayfa
Keywords: “In this book, based on the proceedings of a two-day workshop on experimental archaeology at the Irish Institute of Hellenic Studies at Athens in 2017, scholars, artists and craftspeople explore how people in the past made things, used and discarded them, from prehistory to the Middle Ages. Experimental Archaeology : Making, Understanding, Story-telling is based on the proceedings of a two-day workshop on experimental archaeology at the Irish Institute of Hellenic Studies at Athens in 2017, in collaboration with UCD Centre for Experimental Archaeology and Material Culture. Scholars, artists and craftspeople explore how people in the past made things, used and discarded them, from prehistory to the Middle Ages. The papers include discussions of the experimental archaeological reconstruction and likely past experience of medieval houses, and also about how people cast medieval bronze brooches, or sharpened Bronze Age swords, made gold ornaments, or produced fresco wall paintings using their knowledge, skills and practices. The production of ceramics is explored through a description of the links between Neolithic pottery and textiles, through the building and testing of a Bronze Age Cretan pottery kiln, and through the replication and experience of Minoan figurines. The papers in this volume show that experimental archaeology can be about making, understanding, and storytelling about the past, in the present.” --